GILLIAN M.E. ALBAN, Melusine The Serpent Goddess in A. S. Byatt’s Possession and in Mythology, Lanham, Lexington Books, 2003 & Gillian M.E. Alban, The Medusa Gaze in Contemporary Women’s Fiction, Cambridge, Cambridge Scholars Pub., 2017 - Giallongo, Angela (Rivista di Storia dell’Educazione, 2018)
Review: Gillian M.E. Alban, Melusine The Serpent Goddess in A. S. Byatt’s Possession and in Mythology, Lanham, Lexington Books, 2003, p. 308 Review: Gillian M.E. Alban, The Medusa Gaze in Contemporary Women’s Fiction, Cambridge, Cambridge Scholars Pub., 2017, p. 299